Body weight, cardiac index values, and hematocrit and haemoglobin levels in two turkey commercial lines - Terry M., Verónica K. (2012)
The study aimed to compare the body weight, and cardiac indices, hematocrit and hemoglobin as indicators of cardiac activity of two turkey commercial lines reared at sea level. Thirty five turkeys from each line were used in the study. Body weight (PC) was recorded from the 4th to the 14th week of age where birds were slaughtered. There, blood samples were collected for measuring hematocrit and hemoglobin levels. Also, hearts were collected to determine the following ratios: weight of right ventricle/total ventricle (VD/VT), weight of left ventricle/total ventricle (VI/VT), weight of left ventricle + septum/ total ventricle (VI+S/VT), VI/PC, VD/PC, VI+S/PC, and VT/PC. Body weight and haemoglobin in BUT turkeys were higher (p<0.05) and hematocrit was higher (p<0.05) in Hybrid turkeys. No statistical differences were found on VD/VT, VI/VT, (VI+S)/VT, and VD/PC between lines, but higher values were observed (p<0.05) for VI/PC, (VI+S)/PC, and VT/PC in BUT turkeys, compatible with body weight gain.